The Influence of Internal and External Codes on CSR Practice: The Case of Companies Operating in Serbia - Mijatovic, Ivana S. (Journal of business ethics, 2010)
In this article, our aim is to examine the difference between the corporate social responsibility (CSR) practice of the multinational companies (MNCs) and of the domestic companies operating in Serbia, as well as the influence of internal self-regulations such as statements of corporate values and codes of conduct, and external self-regulations such as the implementation of the ISO 9001 and ISO 14001 standards on CSR practice. The CSR practice is observed in five CSR areas: employee relations, customer relations, environmental practice, community and social involvement, and transparency in business activity. The findings indicate that the CSR practice of the MNCs is significantly different in comparison to domestic companies only in the area of employee relations. Furthermore, the overall results suggest that internal self-regulations have more influence on CSR practice than the implementation of generic management system standards. However, the existence of transparent corporate values, codes of conduct and implemented management systems according to ISO 9001 and ISO 14001 standards does not prove to be strong predictors of CSR performance.